Using sequence analysis to explore the role of motivational talk in consultation - Giles, Grace (2020)
Within the literature, school-based consultation has been conceptualised as an adult behaviour change process (Noell & Gansle, 2014). This study examined the process of consultation through the lens of Motivational Interviewing (MI). To do this, an adapted form of the Motivational Interviewing Sequential Code for Observing Process Exchanges (MI-SCOPE; Martin et al., 2005) was used to code the interaction in consultation between educational psychologists (EPs) and teachers. In total, 1610 verbal utterances were parsed, coded, and analysed over the course of two consultations.